The Effect of Eye-Hand Coordination Training on Underhand Passing Skills in Volleyball in Students of SMPN 17 Pamulang - Ade Chandra Wiguna; Kevin Ramadhan; M Hafid Qolbi; Hendra Jaya; Fikra Azahra; Bambang Suwito Kusumo; Gatot Sukartono (Jurnal Ilmiah Mandala Education (JIME), 2026)
This study aimed to examine the effect of eye–hand coordination training on improving underhand passing skills in volleyball among students of SMPN 17 Pamulang. Underhand passing is a fundamental technique that requires accuracy, strength, and good visual–motor coordination; however, many students still experience difficulties in controlling the direction and force of the ball. This research employed an experimental method using a non-equivalent control group design. The sample consisted of 30 eighth-grade students, divided into an experimental group and a control group, each comprising 15 students. The experimental group received eye–hand coordination training over eight sessions, while the control group followed conventional learning activities. Data were collected through underhand passing skill tests and eye–hand coordination tests administered before (pretest) and after the treatment (posttest). Data analysis included the Shapiro–Wilk test for normality, Levene’s test for homogeneity, Paired Sample t-test, and Independent Sample t-test with a significance level of 0.05. The results indicated a significant improvement in the experimental group between the pretest and posttest (p < 0.05), demonstrating that eye–hand coordination training had a positive effect on underhand passing skills. Furthermore, the comparison between groups showed a significant difference in passing ability, but no significant difference in the coordination variable. Therefore, eye–hand coordination training was proven to be effective in enhancing underhand passing skills of junior high school students. This study recommends that physical education teachers incorporate coordination training as part of volleyball instruction to improve students’ fundamental technical skills.